Consent on Cadaveric Organ Donation in Serbian Law - Baturan, Luka; Samardžić, Stefan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Organ transplantation often presents the only way for efficient treatment of various diseases. According to current legal regulations, in order to use an organ of a deceased person for transplantation, it is necessary that the decedent gave written consent („opting out model”) before death. Under certain circumstances, that consent could be given by close relatives of the decedent, in case that the decedent had not previously explicitly declared that he was against it. These legal regulations do not ensure efficient allocation of scarce goods but they create great social costs. If a legislator accepted “opting in model”, the basic assumption for efficient allocation and increase of social welfare would be provided. The first part of the paper presents the legal framework for organ donation in the Republic of Serbia. The problem of insufficient supply of organs is elaborated in the second part. The third part of the paper contains attempts to increase the level of supply of organs through the promotion of transplantation. In the fourth part of the paper, the effects of different legal solutions are compared, and those are opt-in and opt-out models. The fifth section offers an analysis of criminal-law protection in the area of organ transplantation and its effects on potential organ donors.